Legal Protection of E-Commerce Couriers in Cash on Delivery Payment System - Ndaru Anggara Prabajati; M. Junaidi (Universitas Muhammadiyah Surakarta, 2024)
E-commerce platform purchases provide convenience in transactions, namely with cash (Cash On Delivery) or non-cash through transfer methods or other digital wallets. The Cash On Delivery payment system is a payment method that is made on the spot after the purchase order delivered by the courier is received by the buyer. Payment by this method is considered very easy because no account is needed and can minimise fraud. The method used in this research uses normative research methods. This method is carried out by conducting library research on secondary data sources such as legal regulations, books and other research in the field of law. The role of the courier is as a person appointed by the Company to replace the power of the Company engaged in shipping services. Legal protection of couriers in the Cash On Delivery payment system has been regulated in Article 1601B of the Civil Code. The article regulates the requirements that must be met by couriers and has also been clarified in Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Electronic Information and Transactions.